UJI AKTIVITAS ANTIBAKTERI DARI BLACK GARLIC DENGAN VARIASI WAKTU BERBEDA TERHADAP Streptococcusmutans PENYEBAB KARIES GIGI - Vivi Purwandari; Jon Kenedy Marpaung; Suharyanisa Suharyanisa (Jurnal Farmanesia, 2021)
Dental cariesand gingivitis are the two mostcommon dental and oral diseases in human society. The main cause of both diseasesis a collection of bacteria bound in anorganicmatrix and firmlyattachedtothe tooth surface known as plaque. Black garlicis garlic that has been processed by fermentationat a certaintemperaturefor a long time, resulting in new compounds that have pharmacological effects showing broad antibiotic properties against gram-positiveand gram-negative bacteria, includingstrains that are multi-bacterial. Antibiotic resistance. The purpose of this study was to determine the antibacterial activity of black garlic against Streptococcus mutans bacteria and to determine the differences in the variation of the antibacterial fermentation time of blackgarlicon the antibacterial activity of Streptococcus mutans bacteria. The methodused in this study isanexperimentalmethod (experimentalresearch) to determine the effect of blackgarlic as anantibacterial against Streptococcusmutans. The resultsobtained fromthis study are blackgarlic extract containsalkal oids, flavonoids, tannins, andsaponins. Black garlic extract from variations of 7 days, 12 days, 15 days, and Chlorhexidine had an inhibitoryzone with a strong category while steriledistilled water had an inhibitionzone in the weakcategory.